Observations of Inertia Gravity Waves in the Western Pacific and Their Characteristic in the 2015/2016 Quasi‐Biennial Oscillation Disruption. Issue 22 (25th November 2022) - He, Yang; Zhu, Xiaoqian; Sheng, Zheng; He, Mingyuan; Feng, Yutao
Abstract: The statistical characteristics of inertia‐gravity waves (IGWs) in the troposphere (2–14 km) and lower stratosphere (18–28 km) are analyzed using daily radiosonde observations over six stations in the Western Pacific from 2013 to 2018. Stokes parameter method is used to extract the characteristic parameters of gravity waves (GWs), which are divided into upward and downward propagating waves, and compared with the results of hodograph analysis. In the stratosphere, due to the filtering effect of the background wind field, the IGWs generated in the troposphere mainly propagate eastward with lower frequency range. The tropospheric IGWs have obvious seasonal variation in spectral amplitude and energy, with the maximum in winter and the minimum in monsoon from 2013 to 2018. The stratospheric IGWs are enhanced during phase transition of the quasi‐biennial oscillation, when the enhanced easterly wind appears in the lowest stratosphere, accompanied by enhanced wave energy in the troposphere. During the quasi‐biennial oscillation disruption in late 2015 and early 2016, the tropospheric wave source excites more intense IGWs propagating upward. After reaching the stratosphere, IGWs with slower phase speed are absorbed by the mean flow, dissipating momentum to the lower stratosphere and generating additional enhanced westward forcing, which may have contributed to the development of the easterly wind within the westerly quasi‐biannual oscillation phase. Key Points: Stokes parameter method shows an obvious discrepancy from hodograph analysis when calculating the vertical wave number Over the western Pacific, a large amount of eastward‐propagating inertia‐gravity waves (IGWs) still exist in the stratosphere due to prevailing easterly wind During 15/16D, stratospheric IGWs with lower phase velocity dissipate momentum and produce westward forcing to the mean flow